Polarity, Patriotism, and Dissent in Great War Canada, 1914–1919. - Tough, David (Labour / Le Travail, 2017)
The article reviews the book, "Polarity, Patriotism, and Dissent in Great War Canada, 1914–1919," by Brock Millman.